Relationship of Physico-Chemical and Protective Properties of Vegetable Oils - Kornev, A.Yu.; Knyazeva, L.G. (Journal of Applied Solution Chemistry and Modeling, 2022)
The results of the study of the physicochemical and protective properties of vegetable oils are presented. It was determined that refining reduces the protective efficiency of vegetable oils. Unrefined sunflower and rapeseed oils can be used for corrosion protection in closed unheated rooms in the absence of direct atmospheric precipitation, and their sludge can be used in an open atmosphere.